Donor Influence on the Optoelectronic Properties of N‐Substituted Tetraphenylimidazole Derivatives. Issue 9 (28th February 2023) - Matulaitis, Tomas; dos Santos, Paloma L.; Tsuchiya, Youichi; Cordes, David B.; Slawin, Alexandra M. Z.; Adachi, Chihaya; Samuel, Ifor D. W.; Zysman‐Colman, Eli
Abstract: Three new 1, 2, 4, 5‐tetraphenylimidazole derivatives, 9, 9‐dimethyl‐10‐(4‐(2, 4, 5‐triphenyl‐1H‐imidazol‐1‐yl)phenyl)‐9, 10‐dihydroacridine (DMAC ‐TPI ), 10‐(4‐(2, 4, 5‐triphenyl‐1H‐imidazol‐1‐yl)phenyl)‐10H‐phenoxazine (PXZ‐TPI ), and 10‐(4‐(2, 4, 5‐triphenyl‐1H‐imidazol‐1‐yl)phenyl)‐10H‐phenothiazine (PTZ ‐TPI ), bearing different electron donors at the N1 position of the imidazole were synthesised and characterised. DMAC ‐TPI and PXZ ‐TPI showed narrow emission at λPL of 388 and 418 nm in toluene, and in doped films in Zeonex polymer (1 wt.%) at λPL 381 and 407 nm, respectively, with a full width at half maximum (FWHM) ranging 0.42‐0.44 eV. DMAC ‐TPI and PXZ ‐TPI are predicted to show very low oscillator strength for the low‐energy transitions, which aligns to the observed low photoluminescence quantum yields. Both molecules showed a singlet‐triplet energy gap (Δ E ST of around 1.2 eV) that is much too large to enable reverse intersystem crossing and thermally activated delayed fluorescence. Connecting a donor group to TPI at the N1 position can lead to room temperature phosphorescence (RTP), as the example of PTZ ‐TPI showed. Abstract : Tetraphenylimidazole was explored as a weak electron‐acceptor in donor‐acceptor systems. Blue‐emitting compounds were characterized. While these donor‐acceptor systems turned out to be TADF inactive, one compound showed RTP.